Relaxation Limit for Aw-Rascle System (Journal of Partial Differential Equations, 2014)
We study the relaxation limit for the Aw-Rascle system of traffic flow. For thiswe apply the theory of invariant regions and the compensated compactnessmethod to get global existence of Cauchy problem for a particular Aw-Rascle system with source, where the source is the relaxation term, and we show the convergence of this solutions to the equilibrium state.
Keywords: Aw-Rascle system; relaxation term; compensated compactness; invariant regions